Pain Intensity and Risk of Bone Fracture in Children With Minor Extremity Injuries. - Zanchi, Chiara; Giangreco, Manuela; Ronfani, Luca; Germani, Claudio; Giorgi, Rita; Calligaris, Lorenzo; Norbedo, Stefania; Liccari, Giulio; Cozzi, Giorgio; Barbi, Egidio (Pediatr Emerg Care, 2018)
OBJECTIVES: Injuries are one of the most common causes of pediatric emergency department (ED) visit. The aim of this study was to investigate the relationship between the intensity of pain at the ED visit of children presenting with an extremity injury and the risk of fracture. METHODS: We conducted a retrospective study, considering all patients presenting to the ED of a children's hospital in Italy, with an accidental extremity injury, between May and December 2015. We selected all children aged 8 to 17 years who underwent an x-ray. Children with major, multiple, or nonextremity injuries were excluded. Age, sex, spontaneous and palpation pain, local swelling, time between injury, and medical evaluation were recorded. Sensibility and specificity of spontaneous and palpation pain in detecting a fracture were calculated. RESULTS: We reviewed 994 medical records; of these, 344 (34.6%) reported a fracture. Children's median age was 12 years (interquartile range [IQR], 10-14). Median spontaneous pain at the ED visit was not significantly different between children with and without a fracture: 4.0 (1.0-6.0) and 5 (1.0-6.0), respectively (P = 0.129). Children with mild palpation pain and children without an increase of pain of at least 2 points between spontaneous and palpation pain were fractured in 3.2% and 0.97% of cases, respectively. CONCLUSIONS: In this series, pain intensity in children with a minor extremity injury was not a good marker of fracture. Nevertheless, children with mild palpation pain or with a mild increase of pain between spontaneous and palpation pain had a low risk of fracture.